Importance of Pathya Apathya - Ahara Vihara (wholesome – unwholesome) In Prevention of Prameha - lahari, S V N Sivananda; Kinnera , Rajesh (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda being the oldest system of medicine, which is being practiced with the motive of maintaining the health of healthy individuals and treating the diseased ones by removing the ailments. In Ayurvedic system of medicine for any disease the first line of management is nidana parivarjana (avoiding the cause) which is the primary step. Internal and external medication is of secondary importance. Prameha (diabetes mellitus) is caused by mithya ahara vihara such as sedentary lifestyle, excessive sleep, excessive intake of curd, meat soups of domestic, aquatic, and marshy land animals, milk products, freshly harvested food articles, fresh wine, jaggery preparations and all other kapha promoting substances, laziness, intake of food substances which are cold, unctuous, sweet, fatty and liquid. Mostly sedentary mode of life, viruddha and ahita ahara (incompatible diets) ati matra sevana (excessive intake) of leads to the dreadful disease called Prameha (diabetes mellitus). Any person to prevent prameha roga (diabetes mellitus) must practice healthy way of living by following dinacharya (Daily regimen), rutucharya (Seasonal regimen) by consumption of hita ahara (healthy food) whose intake leads to maintenance of tridoshas in sama avastha (severe phase) so that a person is devoid of any kind of disease. As per Ayurveda acharyas preventing a disease before its onset is done by following hita ahara and vihara (healthy food and lifestyle). After the occurrence of prameha (diabetes mellitus) one must follow the following ahara and vihara like purana shali (old rice), purana godhuma (old wheat) yusha kulutta, mudga (soup) and kalaya (peas), laja manda (scum of parched paddy), purana Madhya (old wine), madhu(honey), takra (butter milk), triphala, lashuna (allium sativum), guda(jaggery), vyayama (exercise) to avoid complications for rest of the life.